"Mato Grosso: celeiro do mundo". Um estudo sobre as relações de poder e as implicações nas políticas públicas - Silva, Lucineia Soares da (Universidade Federal de São Carlos, 2020)
The objective of this research was to understand how the power relations materialized in public policies, from the understanding of the formation of the ideology that calls the State of Mato Grosso as “Celeiro do Mundo” and the image of the farmer-businessman. The State of Mato Grosso was governed, from 2003 to 2010, by one of the greatest representatives of Brazilian agribusiness, Blairo Maggi. To outline the construction of this ideology, we propose as specific objectives: a) to identify the possible cohesion of the dominant group of the agrarian elite in the election of one of its representatives to governor of the State; b) analyze the drafting of Law 7,958 of 2003 (Tax Waiver) and the tax spending policy (those benefited by the policy and the loss of revenue from health and education policies) and, finally, c) analyze social development in the municipalities with the greatest number of beneficiaries from state development programs and other municipalities. The methodology used was quantitative and qualitative. In qualitative analysis, documentary research (public documents and reports), semi-structured script interviews, photo-documentation and geoprocessing were used. The quantitative approach analyzed the number of donors, amounts donated and surrendered, and also a social indicator (HDI and MHDI). The time frame covers public policies in Mato Grosso from the 1960s to 2018, with an emphasis on 2003 - when the Tax Waiver Law was drafted and approved - and 2015 and 2016 - year of the CPI on Tax Waiver. The results show that the public policies implemented for the occupation of Mato Grosso were based on serving the productive system and that there was no prioritization of the agribusiness sector after the election of a representative of the sector, there was continuity and, in a second moment, an expansion to other economic sectors. The research demonstrates the fragility of Law 7,958 / 2003 that instituted the Development Plan of Mato Grosso at its origin, and of the State institutions that should ensure the fulfillment of its objectives. The abundant list of public policies financed by the public fund legitimized and met the accumulation of monopoly, financial and international capital. The revenue waived by virtue of the law directly impacts the financing of health and education because they are linked to the revenue guaranteed by the Federal Constitution: health and education. SUS and Education financing is doubly impaired when a tax waiver policy is instituted by the State when we consider that both have, in an indirect and regressive tax, their greatest source of revenue, the ICMS. In addition to this situation, we have in a state formed by large latifundios the struggle for access to land or for the continuation of possession, in the case of the indigenous people, the record of 11 deaths between 2017 and 2018. Thus, being a “breadbasket of the world” is not in fact to produce food, but commodities for the foreign market, the result of an occupation that did not promote land reform, but the formation of large latifundios and monopolies financed and benefited by public policies and that are always articulating to maintain their privileges.
"Mato Grosso: celeiro do mundo". Estudio sobre relaciones de poder e implicaciones en políticas públicas
Keywords: Estado; Ideologia; Relação de poder; Renúncia fiscal; Políticas públicas; Mato Grosso; State; Power relationship; Tax waiver; Public policy; Ideology; CIENCIAS HUMANAS::SOCIOLOGIA::OUTRAS SOCIOLOGIAS ESPECIFICAS